Company or collector: Farmers’ choice of sales partners in the VietGAP vegetable supply chain? A case study of Southern Central Highlands, Vietnam - Linh, Le Viet; Onaka, Katsutoshi (Asian Journal of Agriculture and Rural Development, 2025)
This study examines the determinants that affect farmers’ choices of consumption partners in the VietGAP vegetable supply chain in Vietnam. A survey involving 161 farming households from the Southern Central Highlands region was conducted, and binary logistic regression was used to analyze the data. The findings indicate that significant factors influencing farmers’ choices include farm size, education level, production experience, income, and family labor. Specifically, farmers with lower education levels, higher family labor participation, and more experience prefer working with collectors for product distribution. In contrast, farmers with higher education levels who adopt advanced technologies, such as greenhouses, automatic irrigation, or fertilization systems, are more likely to collaborate with companies for product distribution. This study highlights the need for targeted support programs to enhance farmers’ knowledge, improve production techniques, and facilitate access to modern technologies. Such initiatives would empower farmers to make more informed business decisions, thereby increasing efficiency within the VietGAP vegetable supply chain. Ultimately, this approach would not only improve the sustainability and profitability of the supply chain but also contribute to the overall development of Vietnam’s agricultural sector.